Assessment of virulence genotypic markers in Yersinia enterocolitica biotype 1A strains of different origins by PCR. - Mastrodonato, Anna Chiara (2019)
Y. enterocolitica B1A comprise a heterogeneous group of strains that encompasses a wide variety of serotypes. They have been considered non-pathogenic microorganisms due to the lack of plasmid and chromosomal virulence determinants that characterize pathogenic strains; however, strains of this biotype are commonly reported not only from healthy individuals, but also from patients with gastrointestinal disorders. The comprehension of pathogenic mechanisms of B1A strains should focus on certain chromosomal virulence determinants associated to adhesion and invasion in intestinal cells (myfA and ail genes), production of heat-stable enterotoxin (ystB), some proteases (hreP) and iron chelating receptor (fepA), all of them related to growth and survival in host during infection. The synthesis of insecticidal toxins (tccC) is also considered a virulence determinant in Y. enterocolitica B1A. In this work, virulence-associated genes such as ystB (146 bp), myfA (272 bp), hreP (757 bp), fepA (438 bp) and tccC (1035 bp) were studied in 23 local Y. enterocolitica B1A strains of different origins (animal, food, environmental and human clinical samples) by PCR. Strains belonging to serotypes O:5 and O:7,8-8-8,19 (six isolates each), O:41,42-41,43 (four isolates), O:5-4,32-4,33 (three isolates), O:6,30-6,31 (two isolates), O:12,25-12,26 and NA (non-agglutinable/non-determined serotype) (one isolate each) were analyzed. DNA extraction was performed by the ―boiling‖ technique and the amplification products were revealed by agarose gel electrophoresis. The frequency of detection of these genes in decreasing order was: fepA and ystB (22/23), hreP (21/23), tccC (3/23) and myfA (1/23). Regarding the relationship between genes and serotypes, fepA, ystB and hreP genes were demonstrated in strains of all serotypes, meanwhile tccC was observed in O:41,42-41,43 and O:7,8-8-8,19 strains, and myfA was only detected in O:7,8-8-8,19 strains. The serotype O:7,8-8-8,19 was associated to the presence of all genes. Regarding the relationship between genes and strain sources, ystB, hreP and fepA were demonstrated in chicken samples (3 isolates), porcine products (five isolates), ground meat (six isolates), human clinical samples (three isolates), and wild boar, hake fillet and wastewater (one isolate each). The myfA gene was observed in porcine skin (one isolate) and tccC was present in porcine skin (two isolates) and wild boar (one isolate). Interestingly, human samples belonged to serotypes O:5 (two isolates) and O:7,8-8-8,19 (one isolate) showed to be carriers of most of the studied genes, except myfA and tccC. Our results suggest the existence of alternative virulence mechanisms in Y. enterocolitica B1A and that the pathogenic potential of this biotype might be strain-dependent.